Investigation of lactose utilization genes in Clostridium acetobutylicum : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biotechnology at Massey University, Palmerston North, New Zealand - Hancock, Kerrie Ruth (Massey University, 1988)
Preparatory to constructing a genomic library of Clostridium acetobutylicum, cell lysis and DNA preparation conditions leading to undegraded DNA were examined. Early to mid-exponential phase cells lysed more readily than cells at late-exponential or stationary phase. Lysis was facilitated by 0.3% w/v glycine in the growth medium. Achromopeptidase was a more effective lytic enzyme than either mutanolysin or lysozyme. All strains of C. acetobutylicum produced high levels of DNase activity, coinciding with the late-exponential and stationary growth phases. Chromosomal DNA isolated from all strains of C. acetobutylicum was rapidly degraded. This degradation was not prevented by the use of various protein inactivating agents. The adverse effect of oxygen and related radicals on the DNA of this strict anaerobe was considered to be responsible. Undegraded DNA was isolated by protecting the cells to be lysed from oxygen. A genomic library of C. acetobutylicum NCIB2951 in the cosmid vector pLAFR1, constituting 3,500 recombinant clones, was prepared. Clones from this library complemented various Escherichia coli auxotrophic mutations, showing that C. acetobutylicum genes are expressible in E. coli. Recombinant clones coding for the β-galactosidase of NCIB2951 were isolated from the genomic library using the chromogenic substrate X-gal. The lacY mutation of HB101 could not be complemented by these clones, suggesting that a classical lac operon system does not exist in C. acetobutylicum. The β-galactosidase (cbg) gene was further subcloned on a 5.2 kb EcoRI fragment, and was expressed when the fragment was cloned in either orientation. Cbg was thus expressed from its own promoter. The cbg gene is inducible by lactose in C. acetobutylicum. When cloned into E. coli, however, this gene was expressed constitutively, the level being unaffected by the presence of the inducer, IPTG or glucose. Six strains of C. acetobutylicum possessed a sequence highly homologous to the cloned β-galactosidase fragment. The β-gatactosidase gene region of NCIB2951 showed only low homology to the DNA from other Gram-positive bacteria (Streptococcus lactis ATCC7962, Streptococcus thermophilus DRI1424, Lactobacillus bulgaricus DRI20056, Lactobacillus helviticus DRI20064), and no detectable homology to DNA from Gram-negative bacteria (E. coli DC272 or Rhizobium loti PN2231). The β-galactosidase activity of the 5.2 kb fragment was inactivated by Tn5 insertion at either of two loci. Locus I (400 bp) was approximately 500 bp from locus II (approximately 3.2 kb). Maxi-cell analysis identified a 100 kDa protein as the β-galactosidase gene product. The 5.2 kb fragment was sequenced and analyzed. Three ORF's were identified. ORF1 (cbgA) coded for the structural β-galactosidase gene. Significant amino acid homology was detected with the amino acid sequences of the lacZ, ebgA (E. coli) and lacZ (Klebsiella pneumoniae). ORF2 (cbgR) coded for a small regulatory protein which shared homology with the amino acid sequence of the "0.3 kb gene" from Bacillus subtilis. ORF3 coded for a truncated protein which shared significant homology with the N-terminal amino acid regions of spo0A and spo0F (B. subtilis), two regulatory proteins of the two-component system. Hence, no lac operon exists in C. acetobutylicum.
Keywords: Clostridium acetobutylicum; Bacterial genetics; Lactose utilisation genes